2020
DOI: 10.1111/pde.14421
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic neuroblastoma mimicking an infantile hemangioma

Abstract: Neuroblastoma is the most common solid tumor malignancy in the first year of life. We present a rare case of a 5-month-old girl with an infraorbital tumor that simulated an infantile hemangioma clinically but was ultimately diagnosed as metastatic neuroblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In addition, Avola et al ( 14 ) reported a SSTM in the outer upper quadrant of the breast, in which the ultrasound showed an internal mottled calcification. The other 3 cases ( 15 - 17 ) showed only a hypoechoic mass on US. At first diagnosis, they were misdiagnosed as neurofibroma, lymphatic malformation, and hemangioma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Avola et al ( 14 ) reported a SSTM in the outer upper quadrant of the breast, in which the ultrasound showed an internal mottled calcification. The other 3 cases ( 15 - 17 ) showed only a hypoechoic mass on US. At first diagnosis, they were misdiagnosed as neurofibroma, lymphatic malformation, and hemangioma.…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic lesions may also present in the periorbital area (Figure 2). 9 A clinical tool for diagnosis may be performed by looking for a distinctive central blanching and erythematous halo that develops 2 to 3 min after stroking the lesion 3 . “Raccoon eyes” (periorbital ecchymosis) from periorbital metastasis, and heterochromia iridis, may also provide clues, though are often absent 3 .…”
Section: The Nonspecific Lump or Bump: Possible Diagnosesmentioning
confidence: 99%
“…Metastatic neuroblastoma presenting as a skin‐colored tumor of the left lower eyelid. Borrowed with permission from Chiloeches Fernández et al (2021) 9 …”
Section: The Nonspecific Lump or Bump: Possible Diagnosesmentioning
confidence: 99%
“…For example, KHE typically responds to sirolimus35 and not to beta blocker therapy, RICH does not require therapy other than supportive care, and IH typically responds to beta blocker therapy. The differential diagnosis should also include other vascular tumors including benign, borderline, and malignant tumors, such as neuroblastoma and angiosarcoma 36–39…”
Section: Differential Diagnosismentioning
confidence: 99%
“…The differential diagnosis should also include other vascular tumors including benign, borderline, and malignant tumors, such as neuroblastoma and angiosarcoma. [36][37][38][39]…”
Section: Differential Diagnosismentioning
confidence: 99%